Protecting the kidneys in lupus nephritis. (October 2011) - Parikh, Samir; Hebert, Lee; Rovin, Brad
Kidney involvement is common in systemic lupus erythematosus. The inciting event in lupus nephritis is immune complex accumulation in the kidneys. While this immune process triggers kidney damage in systemic lupus erythematosus, hemodynamic and metabolic factors activated after this initial event promote chronic, progressive damage to the kidney. Systemic and intraglomerular hypertension, proteinuria, hyperlipidemia, hyperuricemia, uremic acidosis and vitamin D deficiency have all been found to contribute to the progression of kidney disease. The aim of renal protective therapies is to suppress these secondary factors and thereby retard the progression of kidney disease in both active and inactive glomerular disease with residual chronic kidney disease. This can be effectively accomplished through a combination of medications, dietary interventions and lifestyle changes. The aim of this article is to discuss nonimmune therapies that will help retard the progression of kidney disease in lupus nephritis.